Coherent quantum control of internal conversion: in pyrazine via weak field excitation. (17th July 2015) - Grinev, Timur; Shapiro, Moshe; Brumer, Paul
Abstract: Coherent control of internal conversion (IC) between the first ( S 1 ) and second ( S 2 ) singlet excited electronic states in pyrazine, where the S 2 state is populated from the ground singlet electronic state S 0 by weak field excitation, is examined. Control is implemented by shaping the laser which excites S 2 . Excitation and IC are considered simultaneously, using the recently introduced resonance-based control approach. Highly successful control is achieved by optimizing both the amplitude and phase profiles of the laser spectrum. The dependence of control on the properties of resonances in S 2 is demonstrated.